2021
DOI: 10.1002/jor.25068
|View full text |Cite
|
Sign up to set email alerts
|

Difference in orientation of the talar articular facets between healthy ankle joints and ankle joints with chronic instability

Abstract: Since both the talocrural and subtalar joints can be involved in chronic ankle instability, the present study assessed the talar morphology as this bone is the key player between both joint levels. The 3D orientation and curvature of the superior and the posteroinferior facet between subjects with chronic ankle instability and healthy controls were compared. Hereto, the talus was segmented in the computed tomography images of a control group and a chronic ankle instability group, after which they were reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Shape approximation is one of the useful methods to study bone morphology and design ankle implants. Although several studies have measured the morphology of the talar trochlea [ 7 12 ], only a few studies [ 13 16 ] approximated the shape of the talar trochlea from the perspective of TAR implant design. Note that the majority of studies analyzed the shape of the talus in CT images considering that the thickness of the articular cartilage layer of the talar trochlea was shown in the previous literature [ 17 ] to be small and vary slightly, averaging 1.35 ± 0.22 mm in males and 1.11 ± 0.28 in females.…”
Section: Introductionmentioning
confidence: 99%
“…Shape approximation is one of the useful methods to study bone morphology and design ankle implants. Although several studies have measured the morphology of the talar trochlea [ 7 12 ], only a few studies [ 13 16 ] approximated the shape of the talar trochlea from the perspective of TAR implant design. Note that the majority of studies analyzed the shape of the talus in CT images considering that the thickness of the articular cartilage layer of the talar trochlea was shown in the previous literature [ 17 ] to be small and vary slightly, averaging 1.35 ± 0.22 mm in males and 1.11 ± 0.28 in females.…”
Section: Introductionmentioning
confidence: 99%
“… 10 The LHA test is a reliable (ICC, 0.88) and widely used indicator of rearfoot alignment abnormalities in the standing position. 31 In a cohort study by Kleipool et al, 12 participants with CAI had a slightly valgus-directed subtalar joint. Previous studies have reported a higher incidence of ankle sprains for female athletes with a greater calcaneal eversion.…”
Section: Discussionmentioning
confidence: 99%
“…A Sprain can lead to the relaxation or rupture of ligaments around the ankle, resulting in a change in the mechanical properties of the ankle or subtalar joint and uneven force distribution around the subtalar joint, and further lead to instability of the ankle or subtalar joint [ 1 3 ]. Injuries to the subtalar joint are difficult to detect because of the similarities in the mechanism and clinical manifestations of ankle and subtalar joint injuries [ 1 , 4 – 7 ]. At present, researchers are still uncertain about the factors that cause instability of the subtalar joint.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of similar mechanisms of injury and clinical manifestations (both may develop symptoms such as ecchymosis, hematoma, or tenderness on the lateral foot), the involvement of subtalar joint is often neglected [ 1 , 4 , 5 ]. Undetected subtalar joint injuries may result in chronic subtalar instability (CSI) and further cause mechanical and functional instability in the hindfoot, ultimately leading to pain, dysfunction, joint deformity, and PTOA [ 2 , 4 , 6 , 7 ]. The consequences not only increase the financial burden of families but also seriously affect patient quality of life.…”
Section: Introductionmentioning
confidence: 99%